Pengintegrasia Nilai-Nilai Pancasila Dalam Pelajaran Pkn Untuk Meningkatkan Karakter Siswa - Wendi Permata Kasih Telaumbanua (CV. SINAR HOWUHOWU, 2025)
Building national charater though education integrting pancasila values in civics lessons to improve students’character. This study reveals that the integration of pancasila can improve students’character,such as attitudes of nationalism,tolerance,and mutual cooperation. Thus ,this study provides an important contribution in indonesia and pffers an effctive stategy to improve the quality of education. This study aims to determine how to integrate pancasila values in civics lessons. The results pf the study indicate that the integration of pancasila values in civics lessons can impove students’character,such as attitudes,nationalism,tolerance,and mutual cooperation.